Sensitivity Test Of Simple Additive Weighting And Weighted Product Methods For Toddler Nutritional Status - Nadia Dita Salsabila; Ani Dijah Rahajoe; Afina Lina Nurlaili (bit-Tech, 2026)
Toddler nutritional status is an important indicator of child health and development and requires accurate assessment. In Posyandu, nutritional evaluation is often performed manually, which may lead to inefficiencies and inconsistencies when processing large amounts of data. Decision Support Systems (DSS) can assist health workers in conducting more systematic and objective assessments. Previous studies have applied multicriteria decision-making methods such as Simple Additive Weighting (SAW) and Weighted Product (WP) in various decision-making contexts. However, most studies mainly focus on producing ranking results and rarely examine how sensitive these methods are when criteria weights change. In addition, only limited research evaluates these methods using real anthropometric data collected from community health services such as Posyandu. Therefore, this study aims to analyze and compare the sensitivity of the SAW and WP methods in determining toddler nutritional status using empirical anthropometric data. The dataset consists of 412 toddlers collected from Posyandu activities, including gender, age, weight, height, and body mass index, which were converted into nutritional indicators. Sensitivity was assessed by modifying each criterion weight under two scenarios (0.5 and 1) and measuring the percentage change in the resulting preference values. The results show that the SAW method produced a change of 4%, whereas the WP method showed a change of 0.0028%. These findings indicate that SAW is more responsive to weight variations, while WP produces more stable preference values. The results provide empirical insight into the behavior of different multicriteria decision-making methods when applied to real nutritional monitoring data.